Pelatihan Pembuatan Pupuk Organik Cair Berbasis Bakteri Fotosintetik (PSB) bagi Kelompok Tani di Kabupaten Enrekang - Kining, Ekajayanti; Ardat, Muh. Achyar; Rusdin, Rista Astari; Suharman, Suharman; Assidiq, Ilham; Badi, Muslim; Basri, Basri (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This community service aims to transfer the technology of making Liquid Organic Fertilizer (POC) based on Photosynthetic Bacteria (PSB) for the Eran Batu Farmer Group in Pekalobean Village, Enrekang Regency. The method of implementing this community service uses Participatory Rural Appraisal (PRA). This program consists of several stages: (1) Socialization and training, (2) Practice of making POC, (3) Implementation of a demonstration plot for planting yard vegetables, (4) Counseling on product effectiveness, (5) Assistance in product marketing, and (6) Monitoring and evaluation of the program. The results of the community service showed a significant increase in participant knowledge and skills. Pre-test and post-test analysis showed an increase in understanding of 42.59%, with an average score increasing from 68.73 to 98.00. The practice of making POC achieved a success rate of 90%, with 95% of participants reporting a significant increase in independent production capabilities. The implementation of the demonstration plot showed an increase in crop productivity of 22% compared to conventional methods, accompanied by improvements in soil health and plant resistance to pests and diseases. This community service program has succeeded in transferring PSB-based POC technology and encouraging sustainable agricultural practices among farmers of the Eran Batu Farmers Group.